The structure and financing of postgraduation in brazil in the context of development of the public service of education - Godoy Dotta, Alexandre (Universidad Nacional del Litoral, 2015)
The article aims to present the political structure and financing of postgraduation (stricto sensu) in Brazil. It is based on the study of the National Postgraduation Plan 2011-2020, which has as its main purpose to foster the development of the public service of higher education in Brazil. It presents a history of the number of people with the titles of PhD and Master of Science in Brazil from 1960 to 2013. It emphasis the central role of Coordination of Improvement of Higher Education Personnel (CAPES) in structuring public policies to postgraduation. Finally, it indicates the number of scholarships distributed by comparing the investment made in the past governments for the financing of postgraduation in Brazil.